2021
DOI: 10.1371/journal.pone.0256172
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of salivary cortisol, amylase, and chromogranin A to academic stress

Abstract: Salivary biomarkers have been widely used to help diagnose stress, anxiety, and/or depression. This study aimed to compare the responses of three commonly investigated salivary stress biomarkers that represent the hypothalamic-pituitary-adrenal activity (cortisol; sCort) and the sympathetic activity (alpha-amylase; sAA and chromogranin A; sCgA), using academic oral presentation as a model of stress. Twenty postgraduate dental students attended the seminar class as presenter and audience. The presenters’ perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…In this study, heart rate variability measures were performed, calculating the fluctuation in time intervals between subsequent heartbeats, and, thus, providing information regarding neurocardiac function generated by heart–brain interactions and dynamic non‐linear autonomic nervous system processes (McCraty & Shaffer, 2015). Thus, physiological stress—for example, sympathetic nervous system activation and cortisol release—influences memory in various ways (Roozendaal, 2002; Atsak et al, 2016; Gagnon & Wagner, 2016); the academic environment is a reasonable target for associated stress research (Lester et al, 2010; Preuss et al, 2010; Minkley et al, 2017; Myint et al, 2021; Tammayan et al, 2021). To evaluate a timed and well‐defined stressor in academic settings, previous research has mainly focused on acute stress before and during examinations, which consistently resulted in increased cortisol concentrations (Evans et al, 1994; Lacey et al, 2000; Spangler et al, 2002; Weekes et al, 2006; Takatsuji et al, 2008; Preuss et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, heart rate variability measures were performed, calculating the fluctuation in time intervals between subsequent heartbeats, and, thus, providing information regarding neurocardiac function generated by heart–brain interactions and dynamic non‐linear autonomic nervous system processes (McCraty & Shaffer, 2015). Thus, physiological stress—for example, sympathetic nervous system activation and cortisol release—influences memory in various ways (Roozendaal, 2002; Atsak et al, 2016; Gagnon & Wagner, 2016); the academic environment is a reasonable target for associated stress research (Lester et al, 2010; Preuss et al, 2010; Minkley et al, 2017; Myint et al, 2021; Tammayan et al, 2021). To evaluate a timed and well‐defined stressor in academic settings, previous research has mainly focused on acute stress before and during examinations, which consistently resulted in increased cortisol concentrations (Evans et al, 1994; Lacey et al, 2000; Spangler et al, 2002; Weekes et al, 2006; Takatsuji et al, 2008; Preuss et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…More studies are needed regarding the use of sCgA as a stress marker. A previous study from our group also found sCgA to be not as sensitive as sCort or sAA to indicate stress [ 31 ].…”
Section: Discussionmentioning
confidence: 79%
“…A substantial number of large-scale studies demonstrated that increased level of sCort, sAA, and sCgA indicated the activity of the HPA/SAM system in response to various stress models—psychological, physical, academic, post-traumatic, etc. ( 17 , 28 , 38 , 42 – 45 ). Although sCort and sAA are generally used to indicate activation of the HPA/SAM system, there is more evidence that sCgA is mostly used as a SAM system marker ( 33 , 43 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 17 , 28 , 38 , 42 – 45 ). Although sCort and sAA are generally used to indicate activation of the HPA/SAM system, there is more evidence that sCgA is mostly used as a SAM system marker ( 33 , 43 , 45 ).…”
Section: Discussionmentioning
confidence: 99%